Stressful life events and identity development in early and mid-adolescence. (October 2019) - de Moor, Elisabeth L.; Van der Graaff, Jolien; Van Dijk, Marloes P.A.; Meeus, Wim; Branje, Susan
Abstract: Introduction: In the past, stressful life events have been consistently linked to developmental outcomes such as well-being and psychopathological problems. Theory on identity postulates that stressful life events may also predict a regression in identity development. While some support for this link has been found in adult populations, it is important to examine this in adolescence, a time marked by identity development as well as stressful transitions and experiences. Methods: In the present study, we examined whether having to repeat a grade and death of a family member or friend were related to regressive change in educational and relational identity in a sample of 840 Dutch adolescents (49% female, M age W1 = 12.4) drawn from a large ongoing longitudinal study. We also investigated whether the impact of the events was moderated by neuroticism, and parental and peer support. All analyses were controlled for age, educational level, and sex. Results: Results of latent difference score models indicated that experiencing an event did not predict regressions in identity. Congruence between the domain of the event and identity (i.e., educational or relational) did not affect the strength of the effects. Neuroticism and parental and peer support did not significantly moderate this link. However, social support was related to relational and educational identity. Conclusions: The link between stressful events and identity may not be as straightforward as would be expected based on identity theory, as our results did not show evidence for a link between these events and change in identity for all adolescents.